Adesão de cimento autoadesivo em dentina radicular: influência de protocolos de limpeza do espaço para pino - Fonseca Filho, Paulo Fernando Otoni da (2019)
The success of endodontic treatment is due to the biomechanical preparation of root canals, using irrigating solutions that promote disinfection, as well as adequate obturation. However, endodontically treated teeth may be more susceptible to fracture, so the use of intraradicular pins helps in coronary rehabilitation, either with a prosthesis or with a composite resin restoration. These procedures rely on adhesive materials, which, increasingly are similar to enamel and dentin. Since the irrigation solutions used in the walls of the root canal can alter the adhesion strength of the cementing of the fiber pins, it was proposed to evaluate the influence of different irrigation protocols of the prepared spaces for posts in this adhesion. Forty extracted, single root a bovine teeth were selected, and the crowns were sectioned at the cemento-enamel junction. The root canals were prepared with the Reciproc® R50 instrument and filled with gutta-percha and AH Plus® sealer. The specimens were then stored for seven days in a humid oven medium at 37øC. They were then divided into five groups randomly (n = 8) and the posts spaces were prepared with drills under different final irrigation protocols described below: Group I - 2 ml of distilled water (control); Group II - 2 ml 5.25% NaOCl; Group III - NaOCl 5.25% + EDTA 17%; Group IV - NaOCl 5.25% + passive ultrasonic irrigation (PUI); and Group V - NaOCl 5.25% + EDTA 17% + PUI. The pins were cemented with RelyX U200 and the specimens were subjected to the pull-out test. Data were submitted to analysis of variance at one factor (ANOVA), with a significance level of 5%. There was no significant difference between groups, I = 69.25N; II = 78.72; III = 78.91; IV = 80,07N and V = 71,74N, and IV presented higher mean value of applied force for the displacement of the pins. It was concluded that the irrigation protocols tested here had similar results in the tensile strength.